Molecular links between whitesand ecosystems and blackwater formation in the Rio Negro watershed. (15th October 2021) - Simon, C.; Pimentel, T.P.; Monteiro, M.T.F.; Candido, L.A.; Gastmans, D.; Geilmann, H.; da Costa Oliveira, R.; Rocha, J.B.; Pires, E.; Quesada, C.A.; Forsberg, B.R.; Ferreira, S.J.F.; et al.
Abstract: Tropical rivers such as the Rio Negro constitute a major portion of the global aquatic flux of dissolved organic carbon (DOC) entering the ocean, but the exact amount, source contributions and fate of terrestrial DOC remain unknown. We investigated the role of valley and upland whitesand ecosystems (WSEs) and terra firme plateaus in forming blackwater tributaries in the Rio Negro basin to develop novel constraints for the terrestrial export of carbon. 5709 molecular markers from ground- and surface waters of two contrasting valley and upland sites feeding Rio Negro tributaries were identified by ultrahigh resolution mass spectrometry (FT-MS), analyzed by multivariate statistics and compared to known Rio Negro markers. In a Principal Coordinates Analysis, valley and upland DOC molecular composition differed by 78% from plateau DOC, which was characterized by reworked, aliphatic and unsaturated N- and S-containing molecules, while valley and upland DOC contained mainly condensed aromatics, aromatics and oxidized unsaturated structures. Valley and upland samples differed by 10% in molecular DOC composition and by their isotopic content ( 14 C of SPE-DOC, 18 O and 2 H of water) which indicated differences in hydrology and C turnover. Against expectation, markers of widespread whitesand valleys did not emerge as a major source of Rio Negro markers, but specific upland markers did. Pubchem suggested chromene and benzofuran structures as promising candidates for further study. Our findings indicate that the export of molecular markers diverges from expected transport-limited DOC behavior, and thereby opens new avenues for source annotation beyond DOC quantity. Terrestrial DOC from upland whitesand areas is a major source of specific blackwater molecules missing in the regional ecosystem C balance, whereas C export from the whitesand valleys and especially from terra firme plateaus represents mainly recycled and transformed carbon not directly affecting the ecosystem C balance and possibly, the watersheds downstream molecular signature. Our study highlights the potential of high-resolution techniques to constrain carbon balances of ecosystems and landscapes by novel molecular markers. A comparison with other terrestrial DOM datasets indicated molecular similarities with temperate acidic soils and tropical rivers that warrant further analysis of common DOM markers. Implications, limitations, and future challenges are discussed in the light of potential applications of diagnostic molecular links for DOC source annotation and estimation of terrestrial DOM export in the land-to-ocean continuum.